(untitled) (Journal of actual problems of jurisprudence, 2019)
In article especially important problem for the state preservation of human rights in the tyurmakh, colonies and insulators is considered. The previous system of execution of punishments as the subject it is production – economic activity of the state. The problem of ensuring the rights and legitimate interests of the citizens deprived of freedom was considered in the last plan. It was solved in a formal form. Today the international precepts of law occupy an important role in system of the norms providing protection and recognition of the rights of people. Key words: state, execution of the punishment, rights of citizens, imprisonment places, penitentiary safety, safety of the condemned.